Abolish criminology - Saleh-Hanna, Viviane (Abolish criminology, 2022)
This introduction to the edited collection Abolish Criminology contextualizes the times during which the bulk of this book was written. These were years shaped by a 2019 global pandemic that sent so many around the globe into lockdown and the growth of global Black Lives Matter movements against, as the murder of George Floyd and countless Black and Indigenous victims of policing pushed so many disenfranchised and criminalized communities over the edge of putting up and staying quiet. This was also a time of reckoning as many within privileged communities and dominant cultures could no longer turn a blind eye as gruesome images of policing in broad daylight went viral. In this introduction we reflect on that context in relation to the chapters that comprise this book. We provide a summary of each chapter to provide an overview on why the abolition of criminology is necessary and needs attention in the ongoing fights against systemic violence enforced through the interlocking arms of European and white-settler colonialism, heteropatriarchy, and white supremacy.